RFID implementation and study - Lim, Jia Wei (2014)
Radio Frequency Identification (RFID) is a wireless technology that uses radio frequency for data transmission. It had been adopted and integrated into many applications in the recent years. Applications includes Access Management, Logistics Tracking, Contactless Payment and Toll Collection. Different RFID Systems can have different operating frequencies (125 kHz, 13.56 MHz, 900 MHz, 2.4 GHz, etc.) and characteristics (passive/active), which would in turn affect their cost of implementation and field of application.